2013
DOI: 10.1038/cddis.2013.386
|View full text |Cite
|
Sign up to set email alerts
|

The p90 ribosomal S6 kinase (RSK) inhibitor BI-D1870 prevents gamma irradiation-induced apoptosis and mediates senescence via RSK- and p53-independent accumulation of p21WAF1/CIP1

Abstract: The p90 ribosomal S6 kinase (RSK) family is a group of highly conserved Ser/Thr kinases that promote cell proliferation, growth, motility and survival. As they are almost exclusively activated downstream of extracellular signal-regulated kinases 1 and 2 (ERK1/2), therapeutic intervention by RSK inhibition is less likely to produce such severe side effects as those observed following inhibition of the upstream master regulators Raf, MEK and ERK1/2. Here, we report that BI-D1870, a potent small molecule inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…6B). These findings suggest that elevated RSK activity contributes, at least in part, to the seizure susceptibility observed in fragile X mice, although we cannot rule out the possibility that BI-D1870 is acting on other pathways (29).…”
Section: Inhibition Of Rsk Prevents Audiogenic Seizures In Fragile X mentioning
confidence: 86%
“…6B). These findings suggest that elevated RSK activity contributes, at least in part, to the seizure susceptibility observed in fragile X mice, although we cannot rule out the possibility that BI-D1870 is acting on other pathways (29).…”
Section: Inhibition Of Rsk Prevents Audiogenic Seizures In Fragile X mentioning
confidence: 86%
“…15 Much of the research in the quest for E3 inhibitors has been finalized for the p53-HDM2 pathway since p53 is an extremely powerful transcription factor crucial in DNA damage response. [16][17][18][19][20][21] Here, the cellular defense to DNA damage is based on sensors and effectors that activates the cell death pathway, [22][23][24] via p53 [25][26][27][28][29] or its family members. [30][31][32][33][34][35][36][37] Like for our recent Itch inhibitor screening, 14 we believe that in a near future innovative E3 inhibitors will be developed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SL0101 and BI-D1870 were both observed to inhibit glucose uptake, yet by different mechanisms [23]. Moreover, as mentioned above, BI-D1870 can also induce senescence via a p21-dependent mechanism, which is an action not observed for SL0101 [24]. These results suggest that at least one of the inhibitors mediates off-target effects.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, data obtained using these substrates may not be accurate. In another recent article, 10 μM BI-D1870 was shown to induce p21 expression in a RSK-independent manner, and to induce senescence [24]. Furthermore, in vitro studies have shown that PLK1 can be inhibited when BI-D1870 is present at slightly higher concentrations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation